Ionized Gas Outflows from the MAGNUM Survey: NGC 1365 and NGC 4945 - Venturi, Giacomo; Marconi, Alessandro; Mingozzi, Matilde; Carniani, Stefano; Cresci, Giovanni; Risaliti, Guido; Mannucci, Filippo (Frontiers in Astronomy and Space Sciences, 2017)
AGN feedback, acting through strong outflows accelerated in the nuclear region of AGN hosts, is invoked as a key ingredient for galaxy evolution by many models to explain the observed BH-galaxy scaling relations. Recently, some direct observational evidence of radiative mode feedback in action has been finally found in quasars at z >1.5. However, it is not possible to study outflows in quasars at those redshifts on small scales (≲100 pc), as spatial information is limited by angular resolution. This is instead feasible in nearby active galaxies, which are ideal laboratories to explore outflow structure and properties, as well as the effects of AGN on their host galaxies. In this proceeding we present preliminary results from the MAGNUM survey, which comprises nearby Seyfert galaxies observed with the integral field spectrograph VLT/MUSE. We focus on two sources, NGC 1365 and NGC 4945, that exhibit double conical outflows extending on distances >1 kpc. We disentangle the dominant contributions to ionization of the various gas components observed in the central 5.3 kpc of NGC 1365. An attempt to infer outflow 3D structure in NGC 4945 is made via simple kinematic modeling, suggesting a hollow cone geometry.